Local structure and photocatalytic properties of sol–gel derived Mn–Li co-doped ZnO diluted magnetic semiconductor nanocrystals. Issue 27 (26th February 2016) - Dubey, Deepak Kumar; Singh, Digvijay Narayan; Kumar, Shiv; Nayak, Chandrani; Kumbhakar, Pathik; Jha, Sambhu Nath; Bhattacharya, Dibyendu; Ghosh, Anup Kumar; Chatterjee, Sandip
Abstract : The synthesized materials with visible light emission and dye degradation activity can be used effectively in future optoelectronic devices and in water purification for cleaning of dyes. Abstract : The structural, extended X-ray absorption fine structure (EXAFS), X-ray absorption near edge structure (XANES) and photocatalytic properties of sol–gel derived Zn1− y − x Mn y Li x O ( y = 0, 0.02 and x = 0, 0.01, 0.02, 0.03, 0.04, 0.06) nanoparticles (NPs) have been investigated. A small linear increase in lattice parameters ' a ' and ' c ' has been observed which can be attributed to the small distortion of the Zn tetrahedron. From the Mn K-edge XANES data, it can be inferred that Mn exists as Mn 2+ in the 2% Mn-doped ZnO sample. Li doping oxidizes the Mn-cations in the ZnO lattice and hence Mn exists in higher oxidation states (+2 or +3) in (Li, Mn) co-doped ZnO samples. Li doping also favors Mn metal clustering whose signature can be seen in both the Mn K-edge XANES and EXAFS spectra of the (Li, Mn) co-doped samples. UV-light driven degradation of methylene blue (MB) dye aqueous solution has also been demonstrated using pure and doped ZnO and more than 90% dye degradation has been observed within only 90 min of light irradiation. The synthesized materials with visible light emission and dye degradation activity can be used effectively in future optoelectronic devices and in water purification for cleaning of dyes.